Solar and geomagnetic activity dependence of 150-km echoes observed by the Equatorial Atmosphere Radar in Indonesia - Tatsuhiro Yokoyama; Rieko Takagi; Mamoru Yamamoto (Earth, Planets and Space, 2022)
Abstract The occurrence characteristics of 150-km echoes in low-latitude regions are studied using the Equatorial Atmosphere Radar (EAR) in Indonesia. The long-term observation of the 150-km echoes by the EAR enables us to study the occurrence characteristics of 150-km echoes statistically. It is shown that the occurrence rate of the 150-km echoes observed by the EAR shows a semiannual variation with two peaks in solstices and a negative correlation with both the EUV flux and $$Σ$$ Σ Kp index, that is, the solar and the geomagnetic activity. Geomagnetic activity correlates with the occurrence rate of 150-km echoes observed one day after when the $$Σ$$ Σ Kp was measured. However, the occurrence rate is always low during the high solar activity period regardless of the geomagnetic activity. While the seasonal variation and the solar activity dependence of the occurrence of 150-km echoes are consistent with previous studies, this is the first time a negative correlation with geomagnetic activity is reported. Graphical Abstract